2019
DOI: 10.3390/app9183829
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of High-Voltage Electric Field Treatment of Naked Oat Seeds

Abstract: In order to study the mechanism of high-voltage electric field (HVEF) biotechnology, corona discharge produced by a multi-needle-plate HVEF was used to treat naked oat seeds, each treatment dose was divided into two groups, one group was covered with a petri dish cover, the other group was directly exposed to HVEF without a petri dish cover. The scanning electron microscope (SEM) results show that the etching degree of the uncovered group was more serious than that of the covered group, it indicates that ion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Calculation and comparison show that a high voltage and small needle-dielectric plate distance result in high total absorbance, which is in accordance with the above conclusion. Moreover, the RONS of PAW prepared with the needle array-plate DBD are higher than those of discharge It is generally believed that the seeds treated by discharge plasma or PAW can promote the growth and germination rate of plants, but there is no significant difference in the final survival rate of seeds [20,21,32]; therefore, it is impossible to use discharge plasma for mutation breeding. Especially for the seeds of A. adsurgens Pall, because there is a dense wax layer on the epidermis, the discharge plasma can hardly penetrate the seed coat and reach the embryo; however, after discharge plasma etching, RONS in the PAW can reach the embryo site during the seed germination and growth process, and a series of complex processes occur, which can achieve the purpose of mutation breeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation and comparison show that a high voltage and small needle-dielectric plate distance result in high total absorbance, which is in accordance with the above conclusion. Moreover, the RONS of PAW prepared with the needle array-plate DBD are higher than those of discharge It is generally believed that the seeds treated by discharge plasma or PAW can promote the growth and germination rate of plants, but there is no significant difference in the final survival rate of seeds [20,21,32]; therefore, it is impossible to use discharge plasma for mutation breeding. Especially for the seeds of A. adsurgens Pall, because there is a dense wax layer on the epidermis, the discharge plasma can hardly penetrate the seed coat and reach the embryo; however, after discharge plasma etching, RONS in the PAW can reach the embryo site during the seed germination and growth process, and a series of complex processes occur, which can achieve the purpose of mutation breeding.…”
Section: Discussionmentioning
confidence: 99%
“…e needle-plate corona discharge device was widely used in promoting seed germination [20,21], drying [22,23], thawing [24], and other aspects. In order to improve the concentration of plasma active particles and highlight the effect of electric field on water, the DBD structure and the traditional needle array-plate corona discharge structure were combined, and a needle array-plate DBD device was used.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al applied corona discharge produced by a multi-needle-plate HVEF to treat naked oat seeds. According to the Fourier Transform infrared spectroscopy (FTIR) of the seed coat, highvoltage electrostatic fields treatment can form a new absorption peak at 1740 cm −1 , which is closely related to the hydrophilicity of the seed; that is to say, the high-voltage electrostatic fields treatment can improve the hydrophilicity of seeds [47].…”
Section: Seed Germination and Growthmentioning
confidence: 99%
“…In fact, the tion rate and activity of seeds depend on the flux of the excitation magnetic field et al applied corona discharge produced by a multi-needle-plate HVEF to treat n seeds. According to the Fourier Transform infrared spectroscopy (FTIR) of the s high-voltage electrostatic fields treatment can form a new absorption peak at 1 which is closely related to the hydrophilicity of the seed; that is to say, the high electrostatic fields treatment can improve the hydrophilicity of seeds [47]. A high-voltage electrostatic field not only improves the germination rate of seeds, but also improves the physiological indicators of seedlings.…”
Section: Seed Germination and Growthmentioning
confidence: 99%
“…Cold plasma generated by electrical discharges is known for its active species such as UV light, radicals, reactive oxygen species (ROS) and reactive nitrogen species (RNS), and environment-friendly properties, which lays the foundation for its applications in agriculture and food processing (Scholtz et al 2019 ; Song et al 2020 ; Ali et al 2022 ; Esua et al 2021 ; Han et al 2019a ; Pan et al 2021 ; Wu et al 2022 ; Zhu et al 2022 ). There are two different ways of applying cold plasma for seed treatments in agriculture: direct treatments, which are frequently used in previous research and have shown positive impacts on crop growth (de Groot et al 2018 ; Ling et al 2014 ; Velichko et al 2019 ; Xu et al 2019 ), and indirect treatments by using plasma-activated water (PAW) (Esua et al 2021 ; Esua at al. 2022a ; Esua et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%